2020
DOI: 10.35891/ml.v11i2.1872
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Profitabilitas, Islamic Governance Score, Dan Ukuran Bank Terhadap Pengungkapan Islamic Sosial Reporting (Isr) Pada Bank Umum Syariah Di Indonesia

Abstract: The purpose of this study was to analyze the influences of profitability, Islamic Governance Score and the size of banks on the disclosure of Islamic Social Reporting (ISR) in Islamic banks in Indonesia. ISR was an index used to measure the level of social responsibility report of Islamic entities based on the values ​​of Islamic Shari'a. Sample was determined by purposive sampling method according to the research criteria. Based on the sampling technique, among the 11 populations of sharia commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The following is data on Third Party Funds obtained from the monthly financial reports of Bank Bukopin Syariah for the 2014-2022 period. (Amalia Hufil Fadhila & Haryanti, 2020) The determination test aims to determine the size of the relationship between the independent variable and the dependent variable. The Rsquare value obtained is 0.099, which means that Rsquare can measure the correlation of the independent variable with the dependent variable of 0.099 or 09.9%.…”
Section: Research Resultsmentioning
confidence: 99%
“…The following is data on Third Party Funds obtained from the monthly financial reports of Bank Bukopin Syariah for the 2014-2022 period. (Amalia Hufil Fadhila & Haryanti, 2020) The determination test aims to determine the size of the relationship between the independent variable and the dependent variable. The Rsquare value obtained is 0.099, which means that Rsquare can measure the correlation of the independent variable with the dependent variable of 0.099 or 09.9%.…”
Section: Research Resultsmentioning
confidence: 99%
“…According to Nabillah & Oktaviana, (2022), ROA reflects a bank's ability to manage funds and generate profits from investment and financing activities. It represents the ability of the bank to turn acquired funds into returns (Fadhila & Haryanti, 2020;Muchtar & Rofi, 2020).…”
Section: Profitabilitymentioning
confidence: 99%
“…Basically, profitability growth plays an important role in measuring the performance of a specific bank, as it indicates the profit gained by the bank in its operations (Farida & Putriani, 2019). Profitability represents the value that reflects the bank's ability to obtain profit (Fadhila & Haryanti, 2020;Muchtar & Rofi, 2020;Murtadlo & Nuraeni, 2019). Good profitability growth can have an impact on various aspects such as business sustainability and success, attracting investors to invest in the bank, building customer trust, and the ability to face economic challenges (Muchtar et al, 2019).…”
Section: A Introductionmentioning
confidence: 99%
“…ISR has disclosure points that are in line with Islamic principles such as not containing elements of usury, gharar, as well as zakat reporting, sharia compliance status, social aspects, and disclosure of organizational governance activities (Rimayanti, 2017). Haniffa's research (2002) developed by Othman et al (2009) found five points of disclosure of the ISR index, namely funding and investment, products and services, employees, community, environment, and corporate government This disclosure was made because there were found to be limitations in conventional social reporting and could be used for decision-making on Muslim sides and the spiritual satisfaction of investors (Fadhila & Haryanti, 2022) Several factors can influence the disclosure of Islamic Social Reporting. The first factor is Intellectual Capital (Salsabila et al, 2021).…”
Section: Introductionmentioning
confidence: 99%